SUBSTITUSI TEPUNG MOCAF TERHADAP MUTU KERUPUK BIJI DURIAN - Dwi Ari Cahyani (Institute of Computer Science (IOCS), 2023)
Crackers are a food that is loved by people of various circles. The processing of crackers made from mocaf flour and durian seeds is expected to increase the economic value of cassava and durian seeds. The addition of mocaf flour in cracker processing is expected to produce crackers that have quality in accordance with SNI. This study aims to determine the relationship between the addition of mokaf flour and the boiling time of durian seeds to the moisture content, ash content, fat content and protein content contained in the durian seed crackers produced. The ingredients used in this study were mocaf flour and local durian seeds obtained in Banjarnegara regency. This study is an experimental study using RAL as many as 24 experimental units. The data obtained were analyzed using the BNT test ANOVA at a level of 5%. The results of the analysis showed a noticeable difference in the treatment of the components studied. The moisture content contained in the crackers produced is between 4.2% - 6.35%. Ash content of 0.154 % - 0.245 %. Fat content 0.42 % - 0.94%. Protein content of 2.9 % - 6.94 %. The quality of the crackers produced meets the required standards.